Saving creation: faith shaping environmental policy - Rolston, Holmes, 1932-2025, author; Harvard Law School, publisher (Colorado State University. Libraries, 2010)
Religious faith can make a unique contribution to environmental policy. Typically, legislators might expect to formulate a science-based environmental policy. But scientific reasoning is able to offer only partial and value-free guidance. Science, by its very nature, cannot offer enough guidance for the challenges of contemporary environmental policy. Religious faith and religious communities can, and already have begun to, offer precisely what science lacks: a value-laden, unified understanding of creation, humankind, and our obligations as stewards of the Earth. I make this case here by assessing the religious traditions in the United States and Europe, particularly Western monotheism, especially Christianity.
Keywords: religion; ecology; health; quality of life; faith; National Environmental Policy Act; science; management; sustainability; Christianity